Community building as an educational task - Segiet, Waldemar (Kultura-Społeczeństwo-Edukacja, 2020)
Along with the description of contemporary societies, including the indication of clear tendencies towards „individualisation” of lifespan, focusing on subjects that observe themselves with reflection, an issue appears regarding the creation of a community, including the educational one. A peculiar outline of the reflexive modernity is recognised on the basis the ways how individuals achieve social integration. Despite the differentiating forms of social and cultural life, the foundation of the accomplishment of self and the society, is still „community”, which constitutes an encouragement to enter the issue of social (dis)integration, an inspiration allowing to bestow a defined sense on democracy, and socialization processes. Therefore, the need to consider the issues of communities arises, including their confirmation in education. To present a path for social integration, with the full awareness that in modern societies the „common good” ideal is being lost, one should be accompanied by indications regarding education itself. One may reduce them to how the community constituted due to and within education, ensured the integration of all entities concerned, and helped accomplish democracy.